The Rebirth of Cultural Colonialism as Religionswissenschaft: Rudolf Otto's Import House - Alles, Gregory D. (Temenos, 2007)
During his 'world journey' of 1911-1912, Rudolf Otto came to embrace a form of German cultural colonialism which assigned the study of religions a key role. Concern for this colonial program guided his activities unitl the outbreak of World War I, when German colonial ambitions became unrealistic. Although it is difficult to argue that this colonial project had a major impact on Otto's conception of religion, it did alter his scholarly practice with regard to it, transforming him from a liberal systematic theologican into something more akin to whht we know today as a scholar of religions. For 25 years, from 1912 until his death in 1937, much of Otto's professional activity was taken up with importing religions materials from elsewhere, especially from south Asia - mostly texts but also material artefacts. This article reads Otto's colonialism and its rebirth as Religionswissenschaft against the grain of Otto's self-coneption and the coneption of others at the time. While cultural colonialism insisted upon its distance from the activities of the business classes, this article reads those activitites in mercantile terms, In doings so, it suggests that such a re-reading might be profitably applied not just to conceptions of scholarly activity but also to other areas where it has been customary to insist on distance from economic activity, specifically, the way in which scholars of religions have conceived what we usually call religion.